A critique of "understanding the unintended consequences of online teaching" - Kieviet, S. (South African Journal of Higher Education, 2023)
In an ever-changing environment, (of which the “ever-changing” was recently made more prominent due to a world-wide pandemic), humankind either needs to adapt or die. The question however remains: to what extent should we adapt to the “new”? Accepting the fact that each reader would glean and react to different aspects presented in the article “Understanding the unintended consequences of online teaching”, I herewith present my opinion and use this opportunity to raise my concerns regarding the article. The critique of a largely unchallenged characterization of online teaching is a sign of growing intellectual vibrancy in the field which can foster innovative ideas for teaching methods. The objective of this critical note is not to reiterate the case for understanding the unintended consequences of online teaching, rather it is written in the pursuit to expand on what has been published thus far to advance online higher education pedagogy and to highlight the importance and value of academic research in an ever-changing environment.